Memorandum to Chief Regulator Greg Burgfeld from Cheryl Schmit - Cheryl Schmit:::::: (2000)
A memorandum from Cheryl Schmit, co-director of Stand Up For California, pointing out ways the tribe that wished to develop a casino in California does not meet the requirements laid out by the Indian Gaming Regulatory Act of October 17, 1988.